Diabetes Mellitus and Renal Disease: When to Perform a Renal Biopsy? - Matias, P (2009)
Background: Several studies suggest that nondiabetic renal disease (NDRD) is common in patients with diabetes mellitus. The aim of this analysis of renal biopsies in diabetic patients was (a) to assess the prevalence and type of NDRD and (b) to identify its clinical and laboratory predictors. Methods: This retrospective study analysed clinical and laboratory data and biopsy findings in diabetic patients observed by a single pathologist over the past 25 years. Based on biopsy findings, patients were categorised as (i) isolated diabetic nephropathy,(ii) isolated NDRD and (iii) NDRD superimposed on diabetic nephropathy. Results: Of the 236 patients studied, 60% were male and the mean age was 56.3 (±14.2) years. Of these, 91% had known diabetes mellitus at the time of biopsy (13% type 1 and 87% type 2). Isolated diabetic nephropathy was found in 125 (53%), isolated NDRD in 89 (38%) and NDRD superimposed on diabetic nephropathy in 22 (9%) patients. The main indication for biopsy in the three groups was nephrotic proteinuria. Patients with isolated NDRD and NDRD superimposed on diabetic nephropathy presented acute deterioration of renal function more frequently (p<0.001) and had more microhaematuria(p<0.001) as indications for renal biopsy. Focal segmental glomerulosclerosis and membranous nephropathy were the most frequent diagnoses in patients with NDRD. Patients with isolated diabetic nephropathy were younger (p=0.02), presented a longer duration of diabetes mellitus (p<0.001) and had more frequent retinopathy (p<0.001). The prevalence of microhaematuria was higher in patients with isolated or superimposed NDRD (p=0.01). Conclusion: The prevalence of NDRD (either isolated or superimposed on diabetes mellitus) is remarkably frequent in diabetic patients in whom nephrologists consider renal biopsy an appropriate measure. Predictors of NDRD were older age, shorter duration of diabetes mellitus, absence of retinopathy and presence of microhaematuria.